Comparison of Regenerative Tissue Quality following Matrix-Associated Cell Implantation Using Amplified Chondrocytes Compared to Synovium-Derived Stem Cells in a Rabbit Model for Cartilage Lesions. (19th April 2018) - Schmal, Hagen; Kowal, Justyna M.; Kassem, Moustapha; Seidenstuecker, Michael; Bernstein, Anke; Böttiger, Katharina; Xiong, Tanshiyue; Südkamp, Norbert P.; Kubosch, Eva J.
Abstract : Known problems of the autologous chondrocyte implantation motivate the search for cellular alternatives. The aim of the study was to test the potential of synovium-derived stem cells (SMSC) to regenerate cartilage using a matrix-associated implantation. In an osteochondral defect model of the medial femoral condyle in a rabbit, a collagen membrane was seeded with either culture-expanded allogenic chondrocytes or SMSC and then transplanted into the lesion. A tailored piece synovium served as a control. Rabbit SMSC formed typical cartilage in vitro. Macroscopic evaluation of defect healing and the thickness of the regenerated tissue did not reveal a significant difference between the intervention groups. However, instantaneous and shear modulus, reflecting the biomechanical strength of the repair tissue, was superior in the implantation group using allogenic chondrocytes (p < 0.05 ). This correlated with a more chondrogenic structure and higher proteoglycan expression, resulting in a lower OARSI score (p < 0.05 ). The repair tissue of all groups expressed comparable amounts of the collagen types I, II, and X. Cartilage regeneration following matrix-associated implantation using allogenic undifferentiated synovium-derived stem cells in a defect model in rabbits showed similar macroscopic results and collagen composition compared to amplified chondrocytes; however, biomechanical characteristics and histological scoring were inferior.